Webbs An Irish Flora - Parnell, John A. N. (Book collections on Project MUSE., 2011)
This handbook will provide the reader with a clear and reliable means of identifying those plants which grow wild in Ireland. This eighth edition incorporates the latest in botanical research and it reflects contemporary and modern approaches to plant classification based on recent advances in genetics.